THEORETICAL AND METODOLOGICAL ASPECTS OF INTELLECTUAL CAPITAL ASSESSMENT - DUCHYNSKA, NINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
It has been pointed out in the article that intellectual capital has become a key component of the competitiveness of economic entities and national economies in the last quarter of the twentieth century. Economic globalization caused its transformation into businesses` intangible asset. Enterprises began to consider it when calculating their market value, as well as of equity offering, their participation in stock exchange trading. It has been stressed that these processes have proved the need to analyze the nature, structure and evaluation of intellectual capital.The study of intellectual capital assessment makes it possible to note that managers aimed at the efficient management and business development strategies` implementation need to focus on the relevance of intellectual capital`s formation, accumulation, use and evaluation.The article finds out that perceptual methods of intellectual capital assessment are mainly used. It is noted that current methods do not provide for monetary assessment of intellectual capital. They help to solve managerial tasks and allow to diagnose intangible resources of an enterprises.Local problems and attempts to assess intellectual capital have been highlighted. It has been made a conclusion about the need to intensify governmental role in legal framework development for comprehensive system of national intellectual capital assessment.
Keywords: intellectual capital; intellectual capital assessment; perceptual methods